Farm Level Water Footprints, Water Productivity and Nitrogen Use Efficiency in Irrigated Rice under Different Water and Nitrogen Management - Narayan Sahoo, Satyasish Swain; Himadri Nath Sahoo, Gouranga Kar, Ashwani Kumar, Rajbir Sing Alok Kumar Sikka, Sunita Panigrahi (Journal of the Indian Society of Soil Science, 2015)
Attempt was made to study the impact of intermittent irrigations and different nitrogen (N) doses on growth, yield, N use efficiency and water footprints of rice. A rice cultivar, ‘Lalat’ was grown with 3 water regimes in main plots (W1 = continuous flooding of 5 cm, W2 = irrigation after 2 days of water disappearance, W3 = irrigation after 5 days of water disappearance) and 5 N levels in subplots (N1=0 kg N ha-1, N2=60 kg N ha-1, N3=90 kg N ha-1, N4=120 kg N ha-1, N5=150 kg N ha-1). Among water management, lowest mean water footprint (WFP) was observed with W2 but it was at par with W1. Yield, biomass and leaf area also did not significantly differ (P> 0.05) between W1 and W2, but these were significantly lower in W3. These results suggest W2 can reduce water input without affecting rice yields. On the other hand, water productivity in terms of irrigation was higher in W3 though grain yield was less under this treatment. Among N treatments, the lowest average WFP of 1277 m3 t-1 was achieved under 150 kg N ha-1 which was at par with 120 kg N ha-1 but highest WFP of 2532 m3 t-1 was observed when no N was applied. The reduction of WFP with higher dose of N was attributed to mainly increased grain yield of rice. No significant water×nitrogen interactions on biomass, grain yield, WFP, N uptake and N use efficiency were observed.